Transparent microcrystalline glass and preparation method thereof
By optimizing the crystal phase structure and component combination of microcrystalline glass and controlling the grain size, the shortcomings in the chemical strengthening performance and light transmittance of microcrystalline glass are solved, and transparent microcrystalline glass preparation with high transparency and excellent mechanical properties are achieved.
Patent Information
- Application Number
- CN202411437960.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-15
AI Technical Summary
Existing microcrystalline glasses have shortcomings in chemical reinforcement performance and light transmittance, and it is difficult to meet the needs of high-demand display equipment or electronic equipment.
By optimizing the crystal phase structure of microcrystalline glass, the crystal size of high calcium fluoride crystal phase and low lithium silicate crystal phase or lithium disilicate crystal phase are controlled to control the crystal size below 50nm, and the appropriate amount of CaF2, ZrO2 and Transparent microcrystalline glass is prepared by combining two-step heat treatment.
It achieves high transparency and excellent mechanical properties, with light transmittance reaching more than 85.0%, Vickers hardness reaching 600kgf/mm2 or above, and excellent drop resistance and surface pressure performance.
Smart Images

Figure CN119285238A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of glass, and in particular relates to a microcrystalline glass and a preparation method thereof. Background Art
[0002] With the rise of 5G technology, wireless charging technology and electronic products, transparent and high-performance glass materials are widely used in various devices. For example, the glass used in devices such as LED displays must have sufficient strength and chemical stability to withstand regular contact without damage. Glass is also widely used in portable electronic products. Such electronic devices not only have higher requirements on optical properties (including light transmittance, haze and refractive index, etc.), but also have to be able to withstand bending, scratches and impacts. At present, most glass materials use high-aluminum-silicon glass. Although its mechanical properties have been improved after process treatment, it still cannot meet the demand.
[0003] Glass-ceramics is a material that is made by heat treating glass to precipitate crystals inside. Its mechanical properties are better than those of conventional glass, and it has significant advantages in bending resistance, wear resistance, and drop resistance. The mechanical properties of glass-ceramics can be further improved by chemical strengthening. Based on these advantages, glass-ceramics and its products are widely used in display devices and electronic devices with high requirements for drop resistance, pressure resistance, and scratch resistance, especially on the front and back covers of portable electronic devices (such as mobile phones, watches, tablets, etc.). However, the glass-ceramics currently on the market have problems with poor chemical strengthening performance and low light transmittance, which makes it difficult to meet the high requirements of display devices or electronic devices.
[0004] Therefore, developing transparent microcrystalline glass and its products with excellent mechanical properties and high light transmittance has become a research goal. Summary of the invention
[0005] The technical problem to be solved by the present invention is to overcome the deficiencies and defects mentioned in the above background technology and provide a transparent microcrystalline glass with excellent mechanical properties and high light transmittance and a preparation method thereof.
[0006] In order to solve the above technical problems, the technical solution proposed by the present invention is: A transparent microcrystalline glass, whose crystal phases include a main crystal phase and a sub-crystalline phase, the mass of the main crystal phase accounts for 70-98% of all crystal phases, the main crystal phase is a calcium fluoride crystal phase, and the mass of the calcium fluoride crystal phase accounts for 34-60% of the transparent microcrystalline glass, the sub-crystalline phase includes a lithium silicate crystal phase and / or a lithium disilicate crystal phase, the mass of the lithium silicate crystal phase accounts for less than 15% of the transparent microcrystalline glass, and the mass of the lithium disilicate crystal phase accounts for less than 15% of the transparent microcrystalline glass.
[0007] In the above-mentioned transparent microcrystalline glass, preferably, the mass of the main crystalline phase accounts for 77-90% of all crystalline phases, the mass of the calcium fluoride crystalline phase accounts for 43-60% of the transparent microcrystalline glass, and the secondary crystalline phase includes a lithium silicate crystalline phase and / or a lithium disilicate crystalline phase, the mass of the lithium silicate crystalline phase accounts for 2-12% of the transparent microcrystalline glass, and the mass of the lithium disilicate crystalline phase accounts for 1-10% of the transparent microcrystalline glass.
[0008] In the above-mentioned transparent glass-ceramics, preferably, the grain size of the main crystalline phase and the sub-crystalline phase is below 50nm, and more preferably, the grain size of the main crystalline phase and the sub-crystalline phase is below 35nm. Large grain size in glass-ceramics can easily lead to a decrease in the light transmittance of the glass-ceramics, or even devitrification, which will limit the application of glass-ceramics. Therefore, in order to obtain high-transparency glass-ceramics, it is necessary to ensure that the crystal size is much smaller than the wavelength of visible light. The present invention can obtain glass-ceramics with high light transmittance by controlling the grain size of the main crystalline phase and the sub-crystalline phase to be below 50nm, more preferably below 35nm.
[0009] In the present invention, the crystalline phase meets the characteristics of "high calcium fluoride crystalline phase, low lithium silicate crystalline phase and / or lithium disilicate crystalline phase". The polycalcium fluoride crystals reduce the nucleation and crystallization energy of crystal precipitation, which is beneficial to the precipitation and formation of crystals, and can effectively reduce the heat treatment temperature. The addition of the secondary crystalline phase can effectively increase the number of crystal nuclei in the microcrystalline glass and reduce the crystal size. The arrangement of the glass state is disordered, the structure is relatively loose, and the bonding ability is poor. The formation of crystals transforms part of the glass phase into a crystalline phase with higher strength. At the same time, the main and secondary crystals are arranged in order, the structure is more compact, and the performance is enhanced. The present invention is beneficial to improving light transmittance and mechanical properties through the synergistic effect of the main crystalline phase and the secondary crystalline phase.
[0010] In the above-mentioned transparent microcrystalline glass, preferably, its components, by mass fraction, include: SiO2: 30-50%; Al2O3: 15-30%; Li2O: 1-5%; Na2O: 2-6%; CaF2: 5-20%; ZrO2: 1-2%; lanthanide metal oxide: not more than 1%; B2O3: 0-3%; ZnO: 0-2%; MgO: 0-2%; P2O5: 0-7%; clarifier: 0-1%; the clarifier is one or more of Sb2O3, SnO2 and CeO2; the lanthanide metal oxide is one or more of Y2O3, Yb2O3 and La2O3.
[0011] Among the above-mentioned transparent microcrystalline glass, it is more preferred that its components, by mass fraction, include: SiO2: 35-45%; Al2O3: 20-25%; Li2O: 2-5%; Na2O: 2.5-4%; CaF2: 9-16%; ZrO2: 1.5-2%; lanthanide metal oxides: 0.5-0.8%; B2O3: 0-2%; ZnO: 0-1.5%; MgO: 0-1.5%; P2O5: 1-7%; clarifier: 0-0.5%; the clarifier is one or more of Sb2O3, SnO2 and CeO2; the lanthanide metal oxides are one or more of Y2O3, Yb2O3 and La2O3.
[0012] In the above-mentioned transparent microcrystalline glass, preferably, the mass ratio of CaF2 and lanthanide metal oxide is (20-140):1, the mass ratio of ZrO2 and lanthanide metal oxide is (1.5-15):1, the mass ratio of CaF2 and ZrO2 is (7-12):1, and the mass ratio of the total mass of Li2O+Na2O to CaF2 is (0.3-0.6):1.
[0013] In the above-mentioned transparent microcrystalline glass, more preferably, the mass ratio of CaF2 to lanthanide metal oxide is (20-32):1, and the mass ratio of ZrO2 to lanthanide metal oxide is (1.8-4):1.
[0014] In the present invention, simply increasing the CaF2 in the raw material cannot satisfy the crystal phase (high calcium fluoride crystal phase, low lithium silicate crystal phase / and or lithium disilicate crystal phase) and size (less than 50nm) requirements of the present invention. It is necessary to coordinate the amount of other elements in the glass. Our research shows that suitable CaF2 / lanthanide metal oxides can control the amount of lanthanide metal oxides entering into the precipitated calcium fluoride crystals. The size of these lanthanide metal-calcium fluoride crystals is smaller, the grain size is reduced, and the formation of nano-scale microcrystalline glass is promoted; suitable ZrO2 / lanthanide metal oxides can make transparent microcrystalline glass The glass has high transparency. There are vacancy defects in lanthanide metal oxides. Lanthanide metal oxides are added to the glass composition. ZrO2 can enter the vacancy defects of the crystal, making the atomic arrangement in the glass structure more compact and the transparency of the crystal higher. CaF2 / ZrO2 are both crystal nucleating agents. The appropriate amount of crystal nucleating agents is added to generate corresponding crystals. Suitable CaF2 / ZrO2 can provide crystallization sites for the nucleation of crystals. The addition of lithium and sodium oxides can enter the glass network to form crystals. Suitable (Li2O+Na2O) / CaF2 can obtain ideal crystals after crystallization, making the microcrystalline glass transparent. Overall, the present invention can obtain crystals with specific grain sizes and specific main and secondary crystals through the mass ratio of CaF2 and lanthanide metal oxides, the mass ratio of ZrO2 and lanthanide metal oxides, the mass ratio of CaF2 and ZrO2, the total mass of Li2O+Na2O and the mass ratio of CaF2, and the product transparent microcrystalline glass has high light transmittance and good mechanical properties.
[0015] In the above transparent microcrystalline glass, preferably, the mass ratio of SiO2 to Al2O3 is (1.5-2):1, the mass ratio of the total mass of SiO2+Al2O3 to Li2O is (13-20):1, and the mass ratio of Li2O to Na2O is (1-1.4):1. Suitable SiO2 / Al2O3 can make the raw materials have a suitable melting temperature so that the glass is clarified and homogenized; suitable (SiO2+Al2O3) / Li2O can make the glass have a suitable melting temperature and viscosity, promote the clarification of the base glass, and reduce bubbles in the base glass; suitable Li2O / Na2O can make the glass have a suitable crystallization ability and viscosity. Through the above-mentioned limitations, the present invention can change the properties of the glass liquid. Combined with the aforementioned limitations on CaF2, ZrO2 and lanthanide metal oxides, a crystal structure of high calcium fluoride crystal phase, low lithium silicate crystal phase and / or lithium disilicate crystal phase can be prepared. The combination of multiple specific proportions of crystal phases can obtain transparent microcrystalline glass with high light transmittance and excellent mechanical properties.
[0016] As a general technical concept, the present invention also provides a method for preparing the above-mentioned transparent microcrystalline glass, comprising the following steps: preparing a basic glass plate, and then crystallizing the basic glass plate through a two-step heat treatment method to obtain a transparent microcrystalline glass; the two-step heat treatment is to perform a nucleation treatment at a first temperature and to perform a crystal growth treatment at a second temperature higher than the first temperature.
[0017] In the above preparation method, preferably, the first temperature is 500-700°C, the second temperature is 650-850°C, the holding time at the first temperature is 1-10h, and the holding time at the second temperature is 0.5-5h.
[0018] The following is a description of the role of each ingredient: SiO2: SiO2 is an important glass-forming oxide, which forms an irregular continuous network with the structural element of silicon-oxygen tetrahedron [SiO4], becoming the skeleton of glass. SiO2 can reduce the thermal expansion coefficient of glass, and improve the thermal stability, chemical stability, heat resistance, hardness, mechanical strength, viscosity and ultraviolet transparency of glass. However, when the content is high, a higher melting temperature is required, and crystallization may occur.
[0019] Al2O3: Al2O3 is one of the essential components of basic glass and is an intermediate oxide. It exists in glass as a tetraligand [AlO4] and an octaligand [AlO6]. 3+ The higher coordination number (6) makes oxygen tend to be closely arranged, which is conducive to adjusting into regularly arranged crystals. Al2O3 can reduce the crystallization tendency of glass, improve the chemical stability, thermal stability, mechanical strength, hardness and refractive index of glass, reduce the erosion of refractory materials, and help the opacification of fluorides. Al2O3 can control or inhibit the phase separation and crystallization of glass. It is a refractory oxide that can increase the viscosity of glass and make it more difficult to clarify and homogenize the glass. Therefore, the Al2O3 content in the base glass should not exceed 30wt%.
[0020] Li2O: Li2O is a network exometallic oxide that can significantly reduce the melting temperature and viscosity of glass, promote the clarification of base glass, and at the same time reduce the thermal expansion coefficient and crystallization temperature of glass, and reduce the crystallization tendency. A large amount of Li2O increases the crystallization tendency. In general glass, the Li2O content should not exceed 5wt%.
[0021] Na2O: Na2O is an oxide outside the glass network. Sodium ions (Na +) resides in the holes of the glass structure network. Na2O can increase the free oxygen to increase the O / Si ratio in the glass structure and cause bond breaking, thereby reducing the viscosity of the glass and making it easier to melt. It is a good flux for glass. Na2O increases the thermal expansion coefficient of the glass and reduces the thermal stability, chemical stability and mechanical strength of the glass. Using Na2O in the components of microcrystalline glass can reduce the crystallization activation energy and glass crystallization temperature of the glass, weakening the glass crystallization ability and increasing the residual glass phase. Therefore, Na2O cannot be introduced too much, generally not more than 5wt%.
[0022] CaF2: CaF2 is a good nucleating agent. It exists in the high-temperature melt in an ionic state and has great fluidity. During the cooling process of the melt, fluorine ions are precipitated, providing a good crystallization site for the nucleation of crystals. During the precipitation process of fluoride nanoparticles, the changes in the components and structures around them make the grains evenly distributed in the glass matrix, thus avoiding agglomeration. However, too much CaF2 content will cause the microcrystalline glass to be opaque. Therefore, the CaF2 content should not be too much, generally not exceeding 20%.
[0023] ZrO2: ZrO2 is an intermediate oxide that can improve the viscosity, hardness, elasticity, refractive index, and chemical stability of glass, and reduce the thermal expansion coefficient of glass. Glass containing ZrO2 is difficult to melt, and is prone to crystallization when the content exceeds 3%. ZrO2 is used to manufacture glass with good chemical and thermal stability, especially alkali-resistant glass, and high-refractive-index optical glass; ZrO2 is also used as a nucleating agent for microcrystalline glass and a raw material for high-quality refractory materials.
[0024] B2O3: B2O3 is an optional component that helps improve the low-temperature melting property of glass. In small amounts, it helps with melting and enhances chemical stability. However, excessive amounts make clarification difficult, which can lead to devitrification of the glass. Therefore, the B2O3 content should not exceed 3wt%.
[0025] ZnO: ZnO is an intermediate oxide and an optional component. In general, oxygen zinc octahedron is used as the external oxide of the network. When there is enough free oxygen in the glass, oxygen zinc tetrahedron can be formed and enter the structural network of the glass, making the structure of the glass more stable, reducing the thermal expansion coefficient of the glass, and improving the chemical stability, thermal stability and refractive index of the glass. However, excessive use will make the glass easy to crystallize, so the ZnO content does not exceed 2wt%.
[0026] MgO: MgO is a network exo-oxide and an optional component that can slow down the hardening rate of glass and improve the forming properties of glass. MgO can also reduce the crystallization tendency and crystallization rate, increase the high temperature viscosity of glass, and improve the chemical stability and mechanical strength of glass. However, if the MgO content is too high, it may cause a decrease in devitrification resistance, and undesirable crystals will be obtained after crystallization, resulting in a decrease in the performance of dense micro-ceramics. Therefore, the MgO content does not exceed 2wt%.
[0027] P2O5: P2O5 is an optional component that helps improve the low-temperature melting property of glass. It can separate phases in glass to form crystal nuclei and improve the thermal expansion stability of glass during the crystallization process. However, excessive P2O5 content can easily reduce the phase separation of glass and cause devitrification. Therefore, the P2O5 content does not exceed 7wt%.
[0028] Lanthanide metal oxides: their addition can refine the grain size and improve the transmittance of transparent microcrystalline glass, but their dosage needs to be reasonably controlled.
[0029] The transparent microcrystalline glass of the present invention obtains a crystal structure of high calcium fluoride crystal phase, low lithium silicate crystal phase and / or lithium disilicate crystal phase through the optimization of the crystal phase structure. At the same time, in order to prepare the above crystal phase structure, the components of the transparent microcrystalline glass are also rationally optimized and designed. The transparent microcrystalline glass finally prepared has good light transmittance and mechanical properties. After testing, the average light transmittance of transparent microcrystalline products with a thickness of less than 1mm at a wavelength of 400-800nm is more than 85.0%, and the light transmittance of transparent microcrystalline products with a thickness of less than 1mm at a wavelength of 550nm is more than 90%. The surface pressure of transparent microcrystalline products with a thickness of less than 1mm is at least 300MPa, and the Vickers hardness of transparent microcrystalline products with a thickness of less than 1mm is at least 600kgf / mm 2 The drop resistance of transparent microcrystalline glass products with a thickness of less than 1mm is more than 1800mm, the crystallinity is more than 35%, and the grain size is small, less than 50nm.
[0030] Compared with the prior art, the advantages of the present invention are: The transparent microcrystalline glass of the present invention obtains a crystal structure of high calcium fluoride crystal phase, low lithium silicate crystal phase and / or lithium disilicate crystal phase through optimization of the crystal phase structure, so that the microcrystalline glass of the present invention has excellent mechanical properties and transparency. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 This is a physical picture of the transparent microcrystalline glass prepared in Example 1.
[0033] Figure 2 This is the XRD spectrum of the transparent microcrystalline glass prepared in Example 1.
[0034] Figure 3 This is the transmittance curve of the transparent microcrystalline glass prepared in Example 1.
[0035] Figure 4 This is the SEM image of the transparent microcrystalline glass prepared in Example 1.
[0036] Figure 5 This is the transmittance curve of the transparent microcrystalline glass prepared in Comparative Example 2. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with the accompanying drawings and preferred embodiments of the present invention, but the protection scope of the present invention is not limited to the following specific embodiments.
[0038] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0039] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0040] The microcrystalline glass and microcrystalline glass products of the present invention are a type of polycrystalline solid material containing a large number of microcrystalline phases and glass phases. The crystalline phase in the microcrystalline glass is different from the amorphous solid, which can be distinguished by X-ray diffraction and scanning electron microscopy. The microcrystalline glass of the present invention includes crystal phases such as calcium fluoride crystals and lithium silicate. The generation of polycrystalline phases can improve the light transmittance and performance of transparent microcrystalline glass. After repeated experiments and studies, the inventors of the present invention have obtained the transparent microcrystalline glass of the present invention with a lower composition by regulating the content and content ratio of the specific components of the transparent microcrystalline glass to specific values and precipitating the above-mentioned crystalline phase.
[0041] Embodiment 1: This example is used to illustrate that the transparent microcrystalline glass described in the present invention is prepared according to the formula and process parameters in Table 1, and the transparent microcrystalline glass is prepared according to the method described below.
[0042] The method for preparing transparent microcrystalline glass comprises the following steps: configuring raw materials according to the components and mass fractions shown in Table 1 to prepare basic glass; and performing crystallization treatment on the basic glass by a two-step heat treatment method to obtain transparent microcrystalline glass. The crystallization treatment comprises the following steps: performing nucleation treatment at a first temperature, and performing crystal growth treatment at a second temperature higher than the nucleation process temperature. The first temperature of the crystallization treatment is 600°C, and the holding time at the first temperature is 4 hours. The second temperature of the crystallization treatment is 700°C, and the holding time at the second temperature is 0.5 hours.
[0043] Embodiment 2-10: The difference between Example 2-10 and Example 1 lies in the different raw material components, as shown in Table 1 and Table 2 below.
[0044] Comparative Examples 1-4: The difference between Comparative Examples 1-4 and Example 1 lies in the different raw material components, as shown in Table 3 below.
[0045] Table 1: Raw material components and process parameters in Examples 1-4
[0046] Table 2: Raw material components and process parameters in Examples 5-10
[0047] Table 3: Raw material components and process parameters in Comparative Examples 1-4
[0048] The transparent glass-ceramics prepared in Examples 1-10 and Comparative Examples 1-4 were tested, and various performance indicators were tested using the following methods: Refractive index: The refractive index (nd) is tested according to GB / T7962.1-2010 method.
[0049] Grain size: The transparent glass-ceramics is surface treated with HF acid, and the grain size is measured using a scanning electron microscope (SEM).
[0050] Light transmittance: The transparent glass-ceramics was cut into pieces with a thickness of 1 mm and polished, and the average light transmittance at 400-800 nm was measured using a spectrophotometer.
[0051] Vickers hardness: measured by Vickers hardness tester, with a loading force of 200g and a loading time of 15s.
[0052] Ball drop height: Polish a transparent microcrystalline glass with a length, width and height of 150×60×0.6mm, fix it on a rubber frame, and drop a 102g steel ball from a specified height. This is the maximum ball drop height that the transparent microcrystalline glass can withstand without breaking.
[0053] Surface stress: The surface stress of transparent microcrystalline glass is measured using a surface stress meter.
[0054] Density: Density is measured according to Archimedes principle in accordance with GB / T 7962.20-2010.
[0055] The test results are shown in Table 4, Table 5, Table 6 and Figure 1-5 shown.
[0056] Table 4: Performance data in Examples 1-4
[0057] Table 5: Performance data in Examples 5-10
[0058] Table 6: Performance data in Comparative Examples 1-4
[0059] It can be seen from the embodiments and comparative examples that when the raw material components do not meet the restrictions in the present invention, the main crystalline phase is difficult to meet the high calcium fluoride crystalline phase, the low lithium silicate crystalline phase / and or the lithium disilicate crystalline phase, resulting in a visible light transmittance drop to about 80%. At the same time, when the crystalline phase does not meet the high calcium fluoride crystalline phase, the low lithium silicate crystalline phase / and or the lithium disilicate crystalline phase, the Vickers hardness, ball drop height, surface stress, density and crystallinity and other properties are all reduced, thereby affecting the application of transparent microcrystalline glass. When the raw material components meet the restrictions of the present invention, the formation of a polycrystalline phase is promoted, and the main crystalline phase meets the high calcium fluoride crystalline phase, the low lithium silicate crystalline phase / and or the lithium disilicate crystalline phase, which can improve the transmittance of the transparent microcrystalline glass, refine the grain size, and the formation of a polycrystalline phase can improve the performance of the transparent microcrystalline glass.
[0060] Figure 1 This is a physical picture of the transparent microcrystalline glass obtained in Example 1. Figure 1 It can be seen that the microcrystalline glass prepared in Example 1 is transparent. Figure 2 The XRD pattern of the transparent glass-ceramics prepared in Example 1 is as follows: Figure 2 It can be seen that the main crystals of the microcrystalline glass prepared in Example 1 are calcium fluoride crystals, and the content of other crystal phases is relatively small. Figure 3 is the transmittance curve of the transparent microcrystalline glass obtained in Example 1, from Figure 3 It can be seen that the visible light transmittance of the microcrystalline glass prepared in Example 1 is 90%. Figure 4The SEM image of the transparent microcrystalline glass obtained in Example 1 is shown in FIG. Figure 4 It can be seen that the calcium fluoride crystals are granular and have a small particle size. Figure 5 is the transmittance curve of the transparent microcrystalline glass obtained in Comparative Example 2, from Figure 5 It can be seen that the visible light transmittance of Comparative Example 2 is 82%.
Claims
1. A transparent microcrystalline glass, characterized in that: Its crystalline phases include a main crystalline phase and a sub-crystalline phase, the mass of the main crystalline phase accounts for 70-98% of all crystalline phases, the main crystalline phase is a calcium fluoride crystalline phase, and the mass of the calcium fluoride crystalline phase accounts for 34-60% of the transparent microcrystalline glass, the sub-crystalline phase includes a lithium silicate crystalline phase and / or a lithium disilicate crystalline phase, the mass of the lithium silicate crystalline phase accounts for less than 15% of the transparent microcrystalline glass, and the mass of the lithium disilicate crystalline phase accounts for less than 15% of the transparent microcrystalline glass.
2. The transparent microcrystalline glass according to claim 1, characterized in that: The mass of the main crystalline phase accounts for 77-90% of all crystalline phases, the mass of the calcium fluoride crystalline phase accounts for 43-60% of the transparent glass-ceramics, the secondary crystalline phases include lithium silicate crystalline phase and / or lithium disilicate crystalline phase, the mass of the lithium silicate crystalline phase accounts for 2-12% of the transparent glass-ceramics, and the mass of the lithium disilicate crystalline phase accounts for 1-10% of the transparent glass-ceramics.
3. The transparent microcrystalline glass according to claim 1, characterized in that: The grain size of the main crystalline phase and the sub-crystalline phase is less than 50 nm.
4. The transparent microcrystalline glass according to claim 3, characterized in that: The grain size of the main crystalline phase and the sub-crystalline phase is below 35 nm.
5. The transparent microcrystalline glass according to any one of claims 1 to 4, characterized in that: Its components, by mass fraction, include: SiO2: 30-50%; Al2O3: 15-30%; Li2O: 1-5%; Na2O: 2-6%; CaF2: 5-20%; ZrO2: 1-2%; lanthanide metal oxide: no more than 1%; B2O3: 0-3%; ZnO: 0-2%; MgO: 0-2%; P2O5: 0-7%; clarifier: 0-1%; the clarifier is one or more of Sb2O3, SnO2 and CeO2; the lanthanide metal oxide is one or more of Y2O3, Yb2O3 and La2O3.
6. The transparent microcrystalline glass according to claim 5, characterized in that: Its components, by mass fraction, include: SiO2: 35-45%; Al2O3: 20-25%; Li2O: 2-5%; Na2O: 2.5-4%; CaF2: 9-16%; ZrO2: 1.5-2%; lanthanide metal oxides: 0.5-0.8%; B2O3: 0-2%; ZnO: 0-1.5%; MgO: 0-1.5%; P2O5: 1-7%; clarifier: 0-0.5%; the clarifier is one or more of Sb2O3, SnO2 and CeO2; the lanthanide metal oxides are one or more of Y2O3, Yb2O3 and La2O3.
7. The transparent microcrystalline glass according to claim 6, characterized in that: The mass ratio of CaF2 to lanthanide metal oxides is (20-140):1, the mass ratio of ZrO2 to lanthanide metal oxides is (1.5-15):1, the mass ratio of CaF2 to ZrO2 is (7-12):1, and the mass ratio of the total mass of Li2O+Na2O to CaF2 is (0.3-0.6):
1.
8. The transparent microcrystalline glass according to claim 7, characterized in that: The mass ratio of CaF2 to lanthanide metal oxides is (20-32):1, and the mass ratio of ZrO2 to lanthanide metal oxides is (1.8-4):
1.
9. The transparent microcrystalline glass according to claim 6, characterized in that: The mass ratio of SiO2 and Al2O3 is (1.5-2):1, the mass ratio of the total mass of SiO2+Al2O3 and Li2O is (13-20):1, and the mass ratio of Li2O and Na2O is (1-1.4):
1.
10. A method for preparing a transparent glass-ceramic according to any one of claims 1 to 9, characterized in that: The following steps are involved: A base glass plate is prepared, and then the base glass plate is subjected to a crystallization treatment by a two-step heat treatment method to obtain a transparent microcrystalline glass; the two-step heat treatment is a nucleation treatment at a first temperature and a crystal growth treatment at a second temperature higher than the first temperature; The first temperature is 500-700° C., the second temperature is 650-850° C., the holding time at the first temperature is 1-10 h, and the holding time at the second temperature is 0.5-5 h.
Citation Information
Patent Citations
Crystallized glass and method for producing crystallized glass
CN101085699A
High-fracture-toughness microcrystalline glass for mobile phone backboard and preparation method of high-fracture-toughness microcrystalline glass
CN112851122A
Lithium-aluminum-silicon microcrystalline glass as well as strengthening method and application thereof
CN112919813A
Transparent glass ceramic and transparent glass ceramic product
CN115259672A
Glass ceramic and preparation method thereof
CN115925264A